Ceratium Schrank (Dinophyceae) of the National Park Sistema Arrecifal Veracruzano, Gulf of Mexico, with a key for identification - Okolodkov, Yuri B. (Instituto de Ecología, A.C., 2010)
The morphology of 33 species of Ceratium (38 including infraspecific taxa) was studied based on about 600 phytoplankton 20-µm net samples taken from May 2005 through March 2008 at eight sampling stations in the northwestern part of the National Park Sistema Arrecifal Veracruzano, southern Gulf of Mexico. Short descriptions and synonyms are given for each species. Cell size variation with the mean and the standard deviation are given for most species. Twenty-three species are provided with affinities and taxonomic, nomenclatural or biogeographic comments. A dichotomous key for identification of all the species found is presented, and species are illustrated with light microscope photographs and line drawings. Ceratium dens, C. bigelowii, C. limulus, C. tripos f. tripodoides and C. declinatum var. angusticornum are new records for the Mexican waters of the Gulf of Mexico.